Shop Smart, Stay Safe: Marketplace Safety Education for Students at SMP Negeri 8 Jakarta - Vita Briliana; Wasisto Ruswidiono; Deasy Ariyanti Rahayuningsih (International Journal Of Community Service, 2026)
The dominance of the younger generation correlates with high exposure of adolescents to the digital ecosystem (social media and e-commerce), which is saturated with promotions, influencers, and hidden advertisements. This increases the risk of impulsive purchases, fraud, and exposure to online lending/pay later services without adequate understanding. The community service program "Wise Online Shopping" is designed to improve digital literacy and basic financial literacy among junior high school students in Jakarta through an interactive educational approach that aligns with the characteristics of Gen Z/Alpha. The intervention is based on the Stimulus–Organism–Response (S-O-R) framework, with the stimulus being exposure to critical material expected to change students' cognition, emotions, and attitudes, leading to a response of more reflective shopping decisions. The activity was conducted at SMP Negeri 8 Jakarta Pusat on Thursday, December, 11th, 2025 for students in grades VII–VIII (ages 12–14) using a one-group pre-post design with quantitative data (pretest–posttest questionnaires) and qualitative data (observation, written reflection, and group discussion). The material covers online transaction security, identifying advertisements/influencers, scam risks, the dangers of illegal online lending, and child protection aspects in electronic systems. The relevance of the legal aspect is reinforced by Law No. 1 of 2024, which emphasizes the obligation of Electronic System Operators to provide age limit information, child user verification, and abuse reporting mechanisms. The results showed an increase in post-intervention knowledge and a moderate decrease in impulsive buying tendencies, accompanied by increased caution toward influencers and rejection of online lending as a solution for consumption. This program is effective as an initial step for generation Z or Alpha but it requires repeated reinforcement through collaboration between schools, parents, and digital ecosystem policies.